Penerapan PENERAPAN ALUR MERDEKA TERHADAP KEMAMPUAN KOLABORATIF DAN HASIL BELAJAR SISWA DI SMKN 4 SURABAYA - Rahmah, Enis Dyah Fatkhur; Marlena, Novi; Khasanah, Nasriatun; Suprapti; Ariyanti, Elisa (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This study is an action research aimed at determining the influence of the implementation of Merdeka Flow on students' collaborative abilities and learning outcomes. This research was conducted in class XI Digital Business 3 of SMKN 4 Surabaya in the even semester of the Academic Year 2023/2024 with a total of 32 students. This study was conducted in 2 cycles, each comprising planning, action, observation, and reflection. Data collection methods included observation, documentation, and tests. Observations were conducted to assess students' collaborative skills, documentation was used to gather data such as learning materials, student names, instructional documentation, and observation results, and tests were administered to evaluate students' learning progress. The data obtained were analyzed qualitatively for students' collaborative skills and quantitatively for their learning outcomes. Qualitative analysis involved examining indicators of collaborative skills, while quantitative analysis involved calculating achievement percentages and categorizing them. The results showed that students' collaborative skills improved from Cycle I to Cycle II, with an overall rating of Good. Additionally, test results indicated an improvement in learning outcomes from Cycle I, where the pre-test average score increased from 63.59 to 82.03 in the post-test, and in Cycle II, where the pre-test average score increased from 69.69 to 86.56 in the post-test. Consequently, it was concluded that the implementation of Alur Merdeka could enhance both students' collaborative skills and learning outcomes.